POSTUR PADA WANITA HAMIL - Paryono paryono (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2012)
Introduction: Pregnancy effects in changes on all body systems leading to a new balance women and maternal adaptation. Weight gain in pregnant women from both the uterus and breast development generally occurs at the front of the body, but when standing they were still able to maintain a posture that does not face. The purpose of this article is to examine the reasons why pregnant women do not fall to front and how the good attitude of the pregnant woman's body.Materials and Methods: Material of this article are literatures related to pregnancy and the pregnant woman's body p o s t u r e , a n d t h e y w e r e c o l l e c t e d b y l i t e r a t u r e ' s s t u d y a n d l i t e r a r y s t u d y .Discussion: Increased abdominal distension that makes tilting the pelvis forward, decreased abdominal muscle tone and increase weight gain in late pregnancy requires a readjustment spinal curvature. Woman's center of gravity shifts forward. Lumbosakrum normal curve should be more curved and the curvature of the servikodorsal be formed to maintain balance. Assessment of anterior view, lateral and posterior body should include an understanding of the physical structures such as joints and muscles as well as how the meridian pathways. To compensate for the anterior position of the enlarged uterus, lordosis shifting center of gravity to the back of the lower limbs. There is an increased sacroiliac joint mobility, sakrokoksigeal, and pubic joints during pregnancy, possibly due to hormonal changes. Individual assessments will be required to determine the pattern of muscle for every person, especially for those who have musculoskeletal problems.Conclusions and Recommendations: The size of the stomach in a pregnant woman, then the gravity of the body changes. Body to be biased toward the rear , but this position makes your back hurt. Advice for pregnant women in order to maintain your posture as follows: head up